Tidal Current Pattern Modeling in the Wain River Shipping Channel Waters - Huda, Abiyani Choirul; Putri, Destyariani; Nurcholik, Samsu Dlukha; Hasrina (Indonesian Journal of Maritime Technology, 2024)
Semi-enclosed waters surrounded by islands such as Balikpapan Bay, whose waters are influenced by the dynamics of sea tides which affect current speed. Therefore, to understand the pattern and circulation of ocean currents in Balikpapan Bay, especially in the Wain River shipping channel, one way is by hydrodynamic modeling. The water area on the Wain River is an area related to shipping lanes as a shipping route at the Ferry Port. This research on current speed and direction aims to further research on maintaining the depth of shipping lanes due to sedimentation around the Ferry Harbor waters. Therefore, researchers conducted an initial study to create a simulation model of tidal current patterns using Mike 21 software with the aim of finding out what the tidal current patterns and current directions are in the waters of Balikpapan Bay as further data for maintaining the depth of shipping lanes. The data processing used is based on primary data in the form of current speed and direction, and tides and secondary data in the form of depth, current speed and direction, and tides, which are then validated using the RMSE method and to determine the type of tide using the Almilarty method. The results of this research are modeling tidal flow patterns and mapping changes in the morphology of the Wain River. The current speed at high tide ranges from 0.1 m/s to 0.4 m/s, while the current speed at low tide ranges from 0.1 m/s to 0.2 m/s. The depth of the waters around the Wain River is 1 m to 5 m. The tidal type in the waters of the Wain River is a mixed daily double bias.